Effectiveness of hand-hygiene interventions in reducing illness-related absence in educational settings in high income countries: systematic review and behavioural analysis - Hoyle, E; Davies, H; Bourhill, J; Roberts, N; Lee, JJ; Albury, C (Oxford University Press, 2023)
Aim: Control of infection is important to prevent school absence. We aimed to review hand-hygiene interventions in high income countries aiming to reduce gastrointestinal and upper-respiratory tract infectionrelated absence in educational settings, and identify which intervention components are effective.